Actualizaciones en el manejo terapéutico de la urolitiasis. - Añazco Aguirre, Luis Alberto (Machala : Universidad Técnica de Machala, 2020)
Introduction: The urolithiasis is the third more common urologic disease. Around this statistics, the urolithiasis is only surpassed by urinary tracts infections and pathological disorders of the prostate; It is important to remark that the most frequent urologic condition is the renal colic. The etiopathogenesis of the urolithiasis includes supersaturation, nucleation, lack of inhibitors, genetic, dietary and non dietary causes, and urinary-related factors. Most of the renal calculus are expelled spontaneously. Analgesia is the most used and urgent therapeutic procedure. Also, the research shows new medication that has been used by medical expulsive therapies (MET). Objectives: Describe updated pharmacological-therapeutical alternatives related to renal colic treatment, through review of scientific research. Materials and methods: An exhaustive research was done in an academic browser Google Scholar; in databases such as PubMed, Cochrane, Scielo; moreover in medical magazines such as the New England Journal of Medicine. In addition, information from scientific articles that have been published on indexed journals in the last 5 years was considered, between Q1 and Q2 quartile. Conclusion: Besides traditional treatment based on: NSAIDs, opiates, and related medicine to both of them, additional medicine to medical expulsive therapies (MET) has been developed such as alpha 1 blockers (Tamsulosin, Naphtopidil, Silodosin), calcium antagonists (Nifedipine), beta-3 agonist (Mirabegron) and Lidocaine. This additional medicine showed high efficacy during the renal colic pain treatment. The research revealed that both potassium citrate and renalof contributed to the renal calculus dissolution, and also the food consumption is connected directly to the lithium formation.
Introducción: La urolitiasis es la tercera afección urológica más común, superada sólo por las infecciones de vías urinarias y los trastornos patológicos de la próstata; la manifestación más frecuente es el cólico renal. Entre su etiopatogenia está la sobresaturación, nucleación, falta de inhibidores, genética, factores dietéticos, no dietéticos y urinarios. La mayoría de los cálculos se expulsan de manera espontánea. La medida terapéutica urgente más usada es la analgesia. También encontramos nuevos fármacos que se están usando para la terapia médica expulsiva (MET). Objetivo: Describir las alternativas farmacológicas-terapéuticas actualizadas en el manejo del cólico renal, mediante revisión científica. Materiales y métodos: Se realizó búsqueda exhaustiva en base de datos de PubMed, Cochrane, Scielo, revistas médicas como The New England Journal of Medicine, buscadores académicos como Google Scholar, en base a artículos científicos publicados en revistas indexadas durante los últimos 5 años, dentro del Cuartil Q1, Q2. Conclusión: Además del tratamiento tradicional basado en: Aines, Opiáceos y derivados, han surgido otra línea de medicamentos para la terapia medica expulsiva (MET) como son los bloqueadores alfa 1(Tamsulosina, Naftopidil, Silodosina), Calcio antagonistas (Nifedipino), agonista beta-3 (Mirabegron) y la Lidocaína, que demostraron una alta eficacia en el manejo del dolor en el cólico renal. Se evidencio que el Citrato de Potasio evita la formación y el Renalof actua en la disolución de los calculos. También el tipo de alimentación está vinculada directamente en la formación de litos.
Keywords: UROLITIASIS; TRATAMIENTO FARMACOLOGICO; COLICO RENAL